1995
DOI: 10.1901/jaba.1995.28-349
|View full text |Cite
|
Sign up to set email alerts
|

Using Statistical Process Control to Make Data‐based Clinical Decisions

Abstract: Applied behavior analysis is based on an investigation of variability due to interrelationships among antecedents, behavior, and consequences. This permits testable hypotheses about the causes of behavior as well as for the course of treatment to be evaluated empirically. Such information provides corrective feedback for making data-based clinical decisions. This paper considers how a different approach to the analysis of variability based on the writings of Walter Shewart and W. Edwards Deming in the area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…21 To simplify the method, we modified it by using the statistical process control chart. 19,20 We calculated the means of rectified EMG amplitudes and consecutive difference of each point measurement during 100 milliseconds of the pretrigger period. From these values, the 95% limits of variability were derived from two sigma limits (1.77 ϫ mean consecutive deviation) below the mean value.…”
Section: Figure 2 the Effect Of Levetiracetam (Upper Graph) And Placmentioning
confidence: 99%
“…21 To simplify the method, we modified it by using the statistical process control chart. 19,20 We calculated the means of rectified EMG amplitudes and consecutive difference of each point measurement during 100 milliseconds of the pretrigger period. From these values, the 95% limits of variability were derived from two sigma limits (1.77 ϫ mean consecutive deviation) below the mean value.…”
Section: Figure 2 the Effect Of Levetiracetam (Upper Graph) And Placmentioning
confidence: 99%
“…Although visual inspection is the most common method for interpreting single-subject data, including those generated via scatter plots, it is possible that certain complex data arrays may contain patterns that escape visual detection. Therefore, in an attempt to apply precise quantitative rules to the process of interpretation, we constructed an aggregate ''control chart'' (Pfadt & Wheeler, 1995) for each scatter plot. Such charts are often used in statistical process control (SPC), which is a collection of statistical procedures typically applied to industrial manufacturing output to detect patterns of variation in production (see Wheeler & Chambers, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently shown that trend may be present in SCED studies (Solomon, 2014). Given the focus on trend, we do not discuss proposals related to standard deviation bands (i.e., statistical process control; Fisher, Kelley, & Lomas, 2003;Pfadt & Wheeler, 1995) which are more appropriate for stable data. The option tested here is actually better-aligned with recent proposals intended to make dealing with trend a feasible endeavour for applied researchers with no statistical expertise (Parker, Vannest, & Davis, 2014).…”
Section: A Visual Aid Approachmentioning
confidence: 99%